2014
DOI: 10.5194/acp-14-10989-2014
|View full text |Cite
|
Sign up to set email alerts
|

Exploiting simultaneous observational constraints on mass and absorption to estimate the global direct radiative forcing of black carbon and brown carbon

Abstract: Abstract. Atmospheric black carbon (BC) is a leading climate warming agent, yet uncertainties on the global direct radiative forcing (DRF) remain large. Here we expand a global model simulation (GEOS-Chem) of BC to include the absorption enhancement associated with BC coating and separately treat both the aging and physical properties of fossil-fuel and biomass-burning BC. In addition we develop a global simulation of brown carbon (BrC) from both secondary (aromatic) and primary (biomass burning and biofuel) s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
258
1

Year Published

2015
2015
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 241 publications
(283 citation statements)
references
References 109 publications
9
258
1
Order By: Relevance
“…We treat POM aerosol as scattering, although a fraction of POM aerosol may absorb radiation (Kirchstetter et al, 2004;Chen and Bond, 2010;Arola et al, 2011;X. Wang et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…We treat POM aerosol as scattering, although a fraction of POM aerosol may absorb radiation (Kirchstetter et al, 2004;Chen and Bond, 2010;Arola et al, 2011;X. Wang et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Absorption enhancement values of 1.3-3 have been predicted for coated particles (e.g., Bond et al, 2006;Lack et al, 2009;Cappa et al, 2012) although enhancements larger than a factor of 2 have not been measured for ambient aerosol (e.g., Lack et al, 2008;Cappa et al, 2012;McMeeking et al, 2014). Wang et al (2014) suggested that an absorption enhancement factor of 1.1 was appropriate for fossil fuel influenced aerosol and that 1.5 was a more reasonable enhancement factor for biomass-burning-affected aerosol. Biomass burning does not have a consistent influence on either BND or SGP.…”
Section: In Situ Uncertaintiesmentioning
confidence: 99%
“…Alternatively, the column properties retrieved from AERONET measurements and inversions have been widely used to provide a first constraint on modeled vertical aerosol properties (e.g., Sato et al, 2003;Koch et al, 2009;Bond et al, 2013;He et al, 2014;Wang et al, 2014). Use of the AERONET data as an absorption constraint has suggested upscaling of modeled aerosol absorption optical depth (AAOD) values by a factor of 2-6 depending on location (e.g., Bond et al, 2013), although Wang et al (2016) showed that better spatial resolution of models and emission inventories can reduce some of the previously observed model-AERONET discrepancies.…”
mentioning
confidence: 99%
“…South and East Asia are typical regions of atmospheric brown clouds (ABC) (Alexander et al, 2015). Biomass burning has been recognized as a significant contributor to ABC, including forest burning, crop waste burning, traditional religious activities and residential burning in countries like India, China and Thailand (Venkataraman et al, 2006;Yan et al, 2006;mainly absorbs light at UV and short-visible wavelengths (Chen and Bond, 2010;Kirchstetter et al, 2004;Lewis et al, 2008;Sandradewi et al, 2008;Schmid et al, 2006) and this strong spectral dependence has aroused more and more interest recently (Feng et al, 2013;Bahadur et al, 2012;Chung et al, 2012b;Wang et al, 2014;Jethva and Torres, 2011). BrC was ever estimated to contribute about 10-30 % of total absorption of fine particles at shorter wavelengths, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The importance of BC has been widely recognized in recent decades due to its effects of radiative forcing on climate change, while the role of BrC is far from being well known (Jacobson, 2001;Hansen et al, 1997;Haywood et al, 1997;Ramanathan and Carmichael, 2008;Gadhavi and Jayaraman, 2010;Wang et al, 2014). BrC is organic carbon which can absorb light based on a variety of chemical structures like nitrated and/or polycyclic aromatics, phenols, humic-like substances and biopolymers (Jacobson, 1999;Sun et al, 2011;Poschl, 2005).…”
Section: Introductionmentioning
confidence: 99%